Information System Design at SMK YAPIM Taruna Web-Based - Suti, Suti; Karo karo, Siddik (Devitara Innovations, 2023)
Information technology is currently one of the technologies that is developing rapidly at this time, this technology is also used in the world of education. Information systems are used to make work easier, in this case for the world of education, it is used to deliver information online to display school profiles and to manage various academic activities, such as: new student registration, e-learning, extracurricular activities and other activities to attract candidates. students to enroll in a school. With an online system we can save time and space. So that information can be conveyed quickly and accurately. The formulation of the problem contained in this thesis is how to design and build an online learning to use web-based with the aim of making it easier for the online learning acceptance committee to carry out registration of prospective students and make it easier for prospective students to register at the school. The concept applied in the design stage of the web-based online learning Information System. While the programming language used is PHP.